Mechanisms of light adaptation in Drosophila photoreceptors. - Gu, Y.; Oberwinkler, J.; Postma, M.; Hardie, R.C. (Current Biology, 2005)
Phototransduction in Drosophila is mediated by a phospholipase C (PLC) cascade culminating in activation of transient receptor potential (TRP) channels. Ca(2+) influx via these channels is required for light adaptation, but although several molecular targets of Ca(2+)-dependent feedback have been identified, their contribution to adaptation is unclear. By manipulating cytosolic Ca(2+) via the Na(+)/Ca(2+) exchange equilibrium, we found that Ca(2+) inhibited the light-induced current (LIC) over a range corresponding to steady-state light-adapted Ca(2+) levels (0.1-10 microM Ca(2+)) and accurately mimicked light adaptation. However, PLC activity monitored with genetically targeted PIP(2)-sensitive ion channels (Kir2.1) was first inhibited by much higher (>/= approximately 50 microM) Ca(2+) levels, which occur only transiently in vivo. Ca(2+)-dependent inhibition of PLC, but not the LIC, was impaired in mutants (inaC) of protein kinase C (PKC). The results indicate that light adaptation is primarily mediated downstream of PLC and independently of PKC by Ca(2+)-dependent inhibition of TRP channels. This is interpreted as a strategy to prevent inhibition of PLC by global steady-state light-adapted Ca(2+) levels, whereas rapid inhibition of PLC by local Ca(2+) transients is required to terminate the response and ensures that PIP(2) reserves are not depleted during stimulation.